Toxins in pain. Issue 2 (June 2018) - Cardoso, Fernanda C.; Hasan, Mahadhi; Zhao, Tianjiao; Lewis, Richard J.
Abstract : Purpose of review: Pain is a distressing protective sensory experience warning of actual or potential tissue damage. Natural toxins have evolved to exploit pain and related neuronal pathways to facilitate prey capture and for defence, often producing either numbness, paralysis or intense pain by selectively modulating ion channels and receptors in pain pathways. Understanding how toxins modulate pain pathways can enhance our understanding of the physiological and pathological basis of pain. Recent findings: Toxins continue to provide a rich source of unique pharmacological tools and novel drug leads to treat severe neurological disorders, including chronic pain. Recently discovered toxins that selectively modulate Nav 1.7 and Nav 1.1 have helped unravel their involvement in pain signalling. Summary: Toxins have evolved to induce or inhibit pain by targeting a broad range of ion channels and receptors, including NaV, CaV, KV, TRP, ASIC, P2X, α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid, N -methyl-D-aspartate, NET and GPCRs. These toxins bind to specific sites to stimulate or inhibit the activity of these membrane proteins. Toxins continue to yield some of the most exciting leads for developing novel nonopioid analgesics.